Individualized Excel-Based Exams to Prevent Students from Cheating - Ani Wilujeng Suryani (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2020)
The COVID19 pandemic has brought a disruption on education, especially on how courses are delivered in higher education. Higher education providers are forced to go online, irrespective of the IT infrastructure’s availability and the capability of lecturers in delivering online courses. While online learning is perceived as an opportunity for academic integrity breaches, academicians need to ensure that processes are in place to avoid students cheating, especially during the exam. This paper presents an innovative approach based on Excel spreadsheet that allows lecturers to develop individualised exam questions. The method and/or accounting policy, as well as the accounting figures in the exams are automatically tailored based on students’ identification numbers. This program also allows automatic markings for such exams. This type of exam is not perceived complicated by students; but relatively reduce the opportunity to cheat. Hence, it is suggested to be used in the future online exam environment to increase the objectivity of the exam and reliability in exam marking.